Ethnography and Consultee-Centered Consultation: Perfectly Aligned. Issue 1 (2nd January 2022) - Knotek, Steven E.; Dillon, Kerri A.; Toole, Emily N.
Abstract: Consultee-Centered Consultation (CCC) is built upon the use of a constructivist, interactive approach to support conceptual change in consultees. Constructivism is foundational in ethnographic traditions as well and it focuses on understanding socially constructed meaning-making in cultural groups. Given the importance of constructivism in both traditions there is a natural alignment in the use of ethnography to study CCC. This paper illustrates unique contributions ethnography can make to explain and describe the application of CCC, from the social process of problem conceptualization to broadening our understanding of how underserved parents can be engaged as successful consultees. Additionally, it examines how ethnography can advance our theoretical knowledge of the CCC process. The text of four published studies that used ethnography to study CCC were scrutinized. Every article articulated how the ethnographic method was used to pose a research question, present a basis for the research strategy, and examine the studies' findings.